Multislice computed tomography angiography in the diagnosis of cardiovascular disease: 3D visualisations - Sun, Zhonghua (Higher Education Press, 2011)
Multislice computed tomography (CT) has been widely used in clinical practice for diagnosis of cardiovascular disease due to its reduced invasiveness and its high spatial and temporal resolution. As a reliable alternative to conventional angiography, multislice CT angiography has been recognized as the method of choice for detecting and diagnosing head and neck vascular disease, abdominal aortic aneurysm, aortic dissection and pulmonary embolism. In patients with suspected coronary artery disease, although invasive coronary angiography still remains the gold standard, multislice CT angiography demonstrates high diagnostic accuracy, and in selected patients, multislice CT angiography is considered the first line technique. Imaging diagnosis of cardiovascular disease is based on a combination of 2D and 3D visualization tools to enhance the diagnostic value, since reconstructed visualizations provide additional information about the disease extent, accurate assessment of spatial relationship between normal structures and pathological changes, and pre-operative planning and post-procedure follow-up. The aim of this article is to present an overview of the diagnostic performance of various 2D and 3D CT visualizations in cardiovascular disease, including multiplanar reformation, maximum intensity projection, volume rendering and virtual intravascular endoscopy. Recognition of the potential value of these visualizations will assist clinicians to make efficient use of the multislice CT imaging modality for diagnostic management of patients with cardiovascular disease.